(3TQM bGfhf GdYed habG dCMOGK GdJYOjdGJ (B/s - (3CHh TfH, CMeO YHO GdcQjes ((3YeGf(B: s (3OGQ GdKbGaI(B, s, 2009)
(3GdfXQjI GdYGeI dbGfhf GdYed , GfYbGOYbO GdYed , BKGQ YbO GdYed GdaQOj , GfJgGA YbO GdYed GdaQOj , CMcGe YbO GdYed GdLeGYj , GdfRGYGJ GdYeGdjI GdLeGYjI(B.s
(3eQGLY U(B.365s
Keywords: (3YbhO GdYeds; (3bGfhf GdYed h GdYeGds